2006
DOI: 10.1111/j.1524-4725.2006.32110.x
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Carcinoma with Mixed Histology: A Possible Pathogenesis for Recurrent Skin Cancer

Abstract: More than 40% of basal cell carcinomas referred for removal of the residual tumor were BCC-MH. An unsuspected aggressive pathologic pattern of growth may not be detected after a superficial biopsy. Subsequently, the cancer may recur if the initial treatment for the diagnosed nonaggressive tumor subtype is inadequate for the undiscovered aggressive carcinoma. Mohs micrographic surgery is recommended for BCC-MH treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
2
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(127 citation statements)
references
References 81 publications
(125 reference statements)
1
113
2
11
Order By: Relevance
“…The incidence of BCCs with mixed histology is varied between 11% and 43% (54). BCC with mixed histology is most commonly found on the nose, followed by the ear, cheek, and scalp.…”
Section: Bcc With Mixed Histology Bcc With Mixed Histology (Bcc-mh)mentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of BCCs with mixed histology is varied between 11% and 43% (54). BCC with mixed histology is most commonly found on the nose, followed by the ear, cheek, and scalp.…”
Section: Bcc With Mixed Histology Bcc With Mixed Histology (Bcc-mh)mentioning
confidence: 99%
“…Subsequently, the cancer may recur if the initial treatment for the diagnosed nonaggressive tumor subtype is inadequate for the undiscovered aggressive carcinoma. Clinical recurrence of cancer results when there has been persistence of the original tumor secondary to inadequate eradication (54). The recurrence rate for BCC lesions with positive margins calculated from the aggregated data is 27 percent (72).…”
Section: Recurrency Of Bccmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Possible reasons for non-recurrence may include an immune reaction, inflammation or devitalization of the residual tumor tissue. 12 Indeed, some investigators have reported that after a 5 or 10-year follow-up period, not all incompletely excised BCC resulted in recurrences. The highest recurrence rate in BCC was recorded two years after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Morfealiknende og infiltrerende basalcellekarsinomer, derimot, har et mer uforutsigbart forløp med en vekst som kjennetegnes av til dels lange, klinisk ikke-synlige tumorutløpere i én eller flere retninger (11). Mange basalcellekarsinomer har flere histologiske vekstmønstre i en og samme lesjon (12).…”
Section: Histologiunclassified